Parkinson's disease is positively associated with periodontal inflammation - Yılmaz, Melis; Yay, Ekin; Balcı, Nur; Toygar, Hilal; Bolluk Kılıç, Başak; Zırh, Ali; Rivas, Carla Alvarez; Kantarcı, Alpdoğan (Wiley, 2023)
BackgroundParkinson's disease (PA) affects 1% of the global population above 60 years. PA pathogenesis involves severe neuroinflammation that impacts systemic and local inflammatory changes. We tested the hypothesis that PA is associated with periodontal tissue inflammation promoting a greater systemic inflammatory burden. MethodsWe recruited 60 patients with Stage III, Grade B periodontitis (P) with and without PA (n = 20 for each). We also included systemically and periodontally healthy individuals as controls (n = 20). Clinical periodontal parameters were recorded. Serum, saliva, and gingival crevicular fluid (GCF) samples were collected to measure the inflammatory and neurodegenerative targets (YKL-40, fractalkine, S100B, alpha-synuclein, tau, vascular cell adhesion protein-1 (VCAM-1), brain-derived neurotrophic factor (BDNF), neurofilament light chain (NfL). ResultsParkinson's patients in this study had mild to moderate motor dysfunctions, which did not prevent them from performing optimal oral hygiene control. Periodontal parameters and GCF volume were significantly higher in the P and P+PA groups than in the control group. PA was associated with significantly increased bleeding on probing (BOP) compared to P-alone (p < 0.05), while other clinical parameters were similar between P and P+PA groups. In saliva and serum, YKL-40 levels were higher in the P+PA group than in P and C groups (p < 0.001). GCF NfL levels from shallow sites were significantly higher in the P+PA group compared to the C group (p = 0.0462). GCF S100B levels from deep sites were higher in the P+PA group than in healthy individuals (p = 0.0194). ConclusionThe data suggested that PA is highly associated with increased periodontal inflammatory burden-bleeding upon probing and inflammatory markers-in parallel with PA-related neuroinflammation.
Keywords: Etiology; Inflammation; Parkinson’s Disease; Periodontitis; Saliva